Social work practice with children, fourth edition - Webb, Nancy Boyd 1932- (New York The Guilford Press, 2019)
"A leading course text and practitioner resource for over 20 years--now revised and updated--this book presents developmentally and culturally informed methods for helping children in family, school, and community settings. Nancy Boyd Webb offers vital guidance and tools for practitioners. The text demonstrates research-based strategies for working with victims of maltreatment and trauma as well as children affected by poverty, parental substance abuse, bullying, and other adversities. Vivid case examples illustrate the "whys" and "how-tos" of play and family therapy, group work, and school-based interventions. Student-friendly features include thought-provoking discussion questions and role-play exercises. Reproducible assessment forms can be downloaded and printed in a convenient 8 1/2" x 11" size. New to This Edition *Chapter on working with immigrant and refugee children. *Coverage of additional evidence-based practices for intervening with kids. *Discussion of therapist self-care. *Coverage of working with gender-nonconforming children. *Updated for DSM-5, and features up-to-date research on brain development, trauma, and more. "--
"Subject Areas/Keywords: direct practice, family, families, childhood problems, at-risk, adolescents, adolescence, assessments, interventions, psychotherapy, counseling, child abuse, maltreatment, child welfare, neglect, trauma, parents, play therapy, schools, substance abuse, poverty, child development, social workers, textbooks, texts, kids, social work courses, MSW, masters classes, masters students, social work school, LCSW, child protective services, therapists, counselors, practitioners, helping professionals, mental health, transgender, ADHD, emotional and behavioral problems, violence, homelessness, PTSD, parental drug use, domestic violence, community violence, abused children, poor families, dysfunctional, bullying, loss, divorced, immigrants DESCRIPTION A leading course text and practitioner resource for over 20 years--now revised and updated--this book presents developmentally and culturally informed methods for helping children in family, school, and community settings. Nancy Boyd Webb offers vital guidance and tools for practitioners. The text demonstrates research-based strategies for working with victims of maltreatment and trauma as well as children affected by poverty, parental substance abuse, bullying, and other adversities. Vivid case examples illustrate the "whys" and "how-tos" of play and family therapy, group work, and school-based interventions. Student-friendly features include thought-provoking discussion questions and role-play exercises. Reproducible assessment forms can be downloaded and printed in a convenient 8 1/2" x 11" size"--
Revised edition of the author's Social work practice with children, c2011.
Includes bibliographical references (pages 401-436) and index.
Keywords: Social work with children